Public health in 1948 : Remarkable statistics. The first months of the National Health Service
1950-03-31 1950 1950s 8 pages The local health authorities took over their new duties - home nursing and ambulance service - and continued with their old ones. The ambulance service was especially hard pressed and was sometimes abused, but the increase for the most part reflected past inadequacies. Home nursing and home-help schemes had greatly helped in reducing the need for admission to hospital. Moreover, this method of treating the chronic sick at home was, in many ways, an improvement on admission to hospital, since it kept these old people within the family circle, where lay their best hope of real happiness. [P.12] Flexibility of Administration A chapter devoted to the National Health Service outlines the immense amount of preparation before the appointed day, and adds that even on 5th July, 1948, negotiations with the professions were incomplete. It was, therefore, inevitable that some of the administrative arrangements at the beginning of the scheme should be of an interim nature. It was, perhaps, all to the good that this was the case, for such arrangements are the more readily changed. So large an undertaking as the National Health Service must have flexibility in administration to allow for the necessary changes to meet unforeseen problems. [P.117] The National Health Service did not provide from its inception some elaborate new thing, but rather sought to ensure that all necessary services should thenceforth be available without financial obstacles and that there should be the means to develop whatever is lacking in the service in future. More Patients. Some new factors began to appear very soon in the hospitals, mainly arising from changing reactions of the public. Out-patient attendances began immediately to rise. This was a real increase in the number of patients, for the number of attendances per patient did not rise. The increase was particularly noticeable in gynaecology, radiology, pathology and ophthalmology, but affected other specialities as well. It was not unexpected and marked only an accentuation of a change already apparent before the appointed day - a change which is steadily increasing the emphasis on hospitals as centres for diagnosis rather than mainly institutions providing beds for the treatment of the sick. The Chronic Sick. Another early effect of the Service was an increase in demand for beds for the elderly chronic sick, and the situation became extremely difficult during the winter. The rapid development of home help services and the extensive use of home nursing did much to relieve hardship, but there was no doubt that many households and particularly elderly couples living alone needed greater relief than such services could give. The hospitals could not accept as many such cases as was desirable, partly from lack of nurses, partly from lack of beds, and partly because the problem grows steadily with the increase in the proportion of old people in the population. Much had been done recently to rehabilitate the elderly sick in hospitals and return them to their homes, and it might be that the further development of out-patient and home care schemes would both prevent old people from deteriorating to the point where hospital admission is needed and secure earlier admission for those who must have in-patient care. The Hospital Service's Needs. Waiting lists, says the Report, are notoriously inaccurate as a measure of hospital needs, but it is clear that we still need much more hospital service than we can provide, although re-organisation of services within existing buildings and especially the improvement of diagnostic facilities, such as radiological departments, may effect greater improvements than the provision of additional beds. Family Doctors. Of the family doctor service, the Report says that the general experience was that at the beginning doctors immediately began to have larger numbers in their surgeries, although July and August are normally slack months. Some of these calls were unjustifiable, even frivolous; some patients seeking to obtain free supplies of simple medicaments such as are normally kept in any household. The increase was perhaps most marked in areas - 7 - 292/847/5/38